Screen-based Simulation Supporting Problem-based Learning to Improve Football Tactics - Jia, Teng; Sitthiworachart, Jirarat; Morris, John (My University, 2024)
Introduction: This study measured the effect of Problem-Based Learning (PBL) with Screen-Based Simulation (SBS) on undergraduate football tactical decision-making, tactical skills, and student engagement. The Screen-Based Simulation showed tactical scenarios in real games to learners, promoting the identification and analysis of tactical problems in learning. Problem-Based Learning enabled learners to get a deeper understanding of the tactical problems and discuss them effectively. Materials and Methods: Two simulation tools were used in this study. The first one, ‘football match basic offensive and defensive tactical simulation experiment platform,’ is scaffolding in football tactics teaching. Students could use the simulation platform to find tactical problems and learn tactics. The second one, TacticUP, is a screen-based simulation tool to test football tactical decision-making. We used second-year students majoring in physical education at a Chinese university. Seventy-nine students were divided into an experimental group using PBL-SBS and a group taught traditionally. Before the experiment, the tactical decision-making of both groups was assessed in a pretest, and at the end of the six-week experiment, the students were tested again. They also completed a questionnaire on tactical skills and student engagement. Results: There was no significant difference between the pretest scores on tactical decision-making between the two groups (independent-sample t-test, sig = 0.997 > 0.05). However, after the experiment, significantly better improvement was observed in tactical decision-making in the experimental group. The pretest mean score (59) was significantly lower than the post-test one (67) on a scale of 100 (paired sample t-test, sig <0.01). ANOVA showed that the experimental group performed better in all aspects, namely tactical decision-making, tactical skill, and student engagement, than the traditional group (Sig values were all less than 0.01). Conclusion: Compared with traditional teaching, PPL-SBS students performed better in tactical decision-making, tactical skills, and student engagement than students in the traditional teaching group.
Keywords: Decision-making; Football tactics; Problem-based learning; Screen-based simulation; Student engagement; Tactical skills